Psychometric properties of the Indonesian version of the Depression Anxiety Stress Scale: Factor structure, reliability, gender, and age measurement invariance - Muttaqin, Darmawan; Ripa, Serena (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
Measuring instruments that have satisfactory psychometric properties are needed to improve mental health research and services, especially in the effort to measure, identify, and monitor psychological problems experienced by individuals. The purpose of this study is to examine the psychometric properties of the Indonesian version of the Depression Anxiety Stress Scale (DASS). The study involved 1922 participants aged 16-26 in Surabaya, Indonesia. Data collection was made using the convenience sampling method. Testing of the factor structure, reliability, and measurement invariance of the Indonesian version of the DASS was conducted using confirmatory factor analysis, composite reliability, and multi-group analysis. It was found that the bifactor model consisting of specific factors (depression, anxiety, and stress) and general factors (psychological distress) was the best factor structure of the Indonesian version of the DASS (GFI = .954, CFI = .956, RMSEA = .049). In addition, this version has satisfactory composite reliability (.806 – .917) and gender measurement is invariant. The findings indicate that the Indonesian version of the DASS was a valid and reliable measurement tool to measure and compare depression, anxiety, stress, and psychological distress between genders in the Indonesian sample.